PENGARUH LATIHAN HOLLOW SPRINTS TERHADAP KECEPATAN DALAM PERMAINAN TIM SEPAK BOLA SMA NEGERI 2 TAMBANG - Adi Syahdinur; Zainur Zainur; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The problem in this research is that there are still shortcomings when competing and training. This can be seen from the difficulty of players when blocking the opponent's attack speed. This also caused one of the teams to rarely win. Therefore training is needed to increase speed. To fix this problem the author gives the form of the Hollow Sprint exercise. The title raised in this research is ”The Effect Of Hollow Sprints Training On Speed In Game Of Football Team High School 2 Tambang”. The form of this research is (using a one group pretest-posttest design approach) with a sample of 16 people from the Football Team High School 2 Tambang. The instrument used in this research was to use a 30 meter running speed test that aims to know The Effect Of Hollow Sprints Training On Speed In Game Of Football Team High School 2 Tambang. After that, the data is processed statistically, to test normality using the lilifours test at a significant level of 0.05α. The proposed hypotesis was found The Effect Of Hollow Sprints Training On Speed In Game Of Football Team High School 2 Tambang. Based on the analysis of statistical data, it produces pree-test data an Lcount 0.148, a post-test data of Lcount 0.166 and Ltable 0.213, meaning that Lcount < Ltable. Based on the analysis of pree-test and post-test data there are differences in numbers that increase or ride by 3.75. Based on the analysis of the t test produces a Tcount 75 m / sec and a Ttable 1.751, meaning Tcount > Ttable. Thus, be found The Effect Of Hollow Sprints Training On Speed In Game Of Football Team High School 2 Tambang. Key Words: Hollow Sprints Training, Speed.